The People of "Linden Tree Street" and the German Socio-Economic Panel (SOEP) - Hartmut Esser (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Lately I have been receiving numerous requests for contributions to commemorative publications, farewell speeches, and anniversary lectures. I cannot respond to all of these requests, especially since not all of them are as inspiring as the one today: the 25th (in words: the twenty-fifth!) wave of the SOEP! This is indeed an anniversary that should be duly celebrated and honored. The German soap opera "Lindenstrasse" (Linden Tree Street) that was first aired in December 1985 is almost as old as the SOEP. Who could have foreseen in 1984 that there would be so many waves of the SOEP and so many episodes of "Lindenstrasse" following that first one? In the following, I will address four different aspects. First, I will describe some of my impressions while participating in the establishment of the SOEP and its first waves. Second, I will draw attention to the SOEP's role in current public debates (such as the one on migration issues). Third, I will describe my experiences as a SOEP user, and finally, I will elaborate on the great significance of the SOEP for the integration of the social sciences and their empirical methodologies.
Keywords: 330